Desired weight loss and its association with health, health behaviors and perceptions in an adult population with weight excess: One-year follow-up - Bouzas, Cristina; Bibiloni, Maria del Mar; Garcia, Silvia; Mateos, David; Martínez-González, Miguel Ángel; Salas-Salvadó, Jordi; Corella, Dolores; Goday, Albert; Martínez, J. Alfredo; Alonso-Gómez, Ángel M.; Wärnberg, Julia; Vioque, Jesús; et al. (Frontiers in Nutrition, 2022)
Background Metabolic syndrome (MetS) worsens quality of life and increases mortality. Dissatisfaction with weight in patients with MetS may modify the effect of lifestyle interventions to achieve changes in health-related behaviors. Objective To assess 1-year changes in cardiovascular risk scores, self-perceived general health and health-related behaviors according to observed changes in desired weight loss during the first year of intervention in a large cardiovascular prevention trial. Design Prospective analysis of the PREDIMED-PLUS trial, including 5,499 adults (55–75 years old) with overweight or obesity at baseline. Methods The desired weight loss was the difference between ideal and measured weight. Tertiles of change in desired weight loss (1 year vs. baseline) were defined by the following cut-off points: ≥0.0 kg (T1, n = 1,638); 0.0 to −4.0 kg (T2, n = 1,903); ≤−4.0 kg (T3, n = 1,958). A food frequency questionnaire assessed diet and the Minnesota-REGICOR questionnaire assessed physical activity. The Framingham equation assessed cardiovascular risks. The changes in the severity of MetS were also assessed. The Beck Depression Inventory assessed depressive symptoms and the SF-36 assessed health-related quality of life. Data were analyzed using general linear models. Results BMI decreased at T2 and T3 (T1: 0.3, T2: −0.7, T3: −1.9). The most significant improvement in diet quality was observed at T3. Cardiovascular risk decreased at T2 and T3. Mean reductions in MetS severity score were: −0.02 at T1, −0.39 at T2 and −0.78 at T3. The perception of physical health increases in successive tertiles. Conclusions In older adults with MetS, more ambitious desired weight loss goals were associated with improvements in diet, cardiovascular health and perceived physical health during the first year of a healthy lifestyle intervention programme. Weight dissatisfaction needs to be considered by health professionals. Clinical trial registration http://www.isrctn.com/ISRCTN89898870, identifier 89898870.